Evolution from the nuclides to the chemical elements - Komarov, N. S. (Одеські астрономічні публікації, 2017)
The chemical evolution of Universe and it's objects (from grains to black holes) were of main goal of recent reviews and investigations. The evolution of chemical elements and their isotopes (early nuclides) discussed as indicator of evolution of Universe from Big Bang to now. The problem of determination of contents of chemical elements and their isotopes in atmospheres of cool giants to use method of the models of atmospheres and the synthetic spectra is discussed briefly. The determination of fundamental characteristics of cool stars (the effective temperature Teff , surface gravity lgg, metallicity [Fe/H]) are discussed too. The evolution of all nuclides heaver 4He (with the exception, possibly, of most lightest nuclides - 6Li, 7Li, 9Be, 10B, 11B) are caused of these stars.